1 The Materiality of Everyday Life: An Introduction. Issue 1 (September 2015) - Overholtzer, Lisa; Robin, Cynthia; Overholtzer, Lisa; Robin, Cynthia
ABSTRACT This volume explores the analytical productivity of the convergence of two bodies of theory: materiality, defined here as the mutually constitutive relationships between people and the material world, and everyday life, conceived of as the ordinary practices that comprise most of human existence. An engagement with materiality and everyday life reveals three interventions critical to archaeological research. First, archaeological studies of the somewhat ethereal concept of materiality benefit from a grounding in the context of material engagements in everyday life. Second, the seemingly mundane and ordinary material practices of everyday life are of crucial significance for society in such varied arenas as politics, commerce, and cosmology. Third, the study of the materiality of everyday life necessarily implicates fruitful attention to multiple social and temporal scales.